Energy a beginner's guide - Smil, Vaclav (Oxford Oneworld, 2009)
As Einstein pointed out in his famous equation, E=MC2, all matter can be described as energy. It is everywhere; it is everything. In this engaging book, prolific author and academic Vaclav Smil provides an introduction to the far-reaching term and gives the reader a greater understanding of energy's place in both past and present society. Starting with an explanation of the concept, he goes on to cover such exciting topics as the inner workings of the human body, and the race for more efficient and environmentally friendly fuels. With global warming becoming a mainstream political issue, this guide will help shed light on the science behind it and efforts to prevent it, and how our seemingly insignificant daily decisions affect energy consumption. Whether you're after insight or dinner table conversation, "Energy: A Beginner's Guide" will amaze and inform, uncovering the science behind one of the most important concepts in our universe.
ix, 218 p. : ill. ; 20 cm.
Keywords: Force and energy